Precision Medicine in Autoimmune Thyroiditis and Hypothyroidism - Ferrari, Silvia Martina; Ragusa, Francesca; Elia, Giusy; Paparo, Sabrina Rosaria; Mazzi, Valeria; Baldini, Enke; Benvenga, Salvatore; Antonelli, Alessandro; Fallahi, Poupak (Frontiers in Pharmacology, 2021)
Autoimmune thyroid diseases (AITD) are T-cell-mediated organ specific autoimmune disorders, deriving from an altered response of the immune system that leads to the immune attack to the thyroid. Hashimoto’s thyroiditis (HT) and Graves’ disease (GD) are the two principal AITD clinical presentations. Hypothyroidism and thyrotoxicosis are, respectively, the clinical hallmarks of HT and GD. Patients with autoimmune thyroiditis are treated daily with synthetic L-thyroxine (L-T4) at the dose of 1.5–1.7 μg/kg. Various L-T4 formulations are commercially available (tablet, liquid solution, or soft gel capsule). L-T4 in tablets is generally prescribed to treat hypothyroidism, whereas the liquid formulation, or soft gel capsules, can be administered in hypothyroid patients in case of malabsorption or in patients in therapy with drugs interfering with L-T4 absorption. Furthermore, myoinositol has a crucial role in thyroid autoimmunity and function. Clinical studies reported a significant decline in TSH and antithyroid autoantibodies levels after treatment with myoinositol + selenium in patients with subclinical hypothyroidism and autoimmune thyroiditis. Moreover, thyroidectomy can be rarely recommended in patients with autoimmune thyroiditis, with cosmetic reasons for a goiter, or with important signs or symptoms of local compression, or nodular disease with a “suspicious” cytology for malignancy. Furthermore, a recent randomized trial suggested that total thyroidectomy can improve quality of life and fatigue, while medical therapy did not. In this review, we overview currently available evidence in personalized medicine in patients with autoimmune thyroiditis and hypothyroidism. Further research is needed in larger population to investigate the effect of these new treatments on quality of life.